Penerapan Bimbingan Kelompok Dalam Membentuk Kepribadian Remaja Dipanti Asuhan Griya Yatim dan Dhuafa Bukittinggi - A, Angreni; Putra, Dodi Pasila; Hendri, Budi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Group guidance is an activity carried out in the form of discussions by utilizing dynamics, which supports individual development to reach the next stage of the task, because every human being certainly has a different personality, character, behavior and habits. This causes individuals to experience difficulties in adapting to the environment, as stated in Q.S Al-Hujarat verse 13 explaining that humans must have sensitivity in social life. The aim of the research is to find out whether the implementation of group guidance services is effective in shaping teenagers' personalities. The type of research is qualitative based on facts and the results of observations in the field using mask techniques. The sources and research subjects are the orphanage administrators and group members. The results of the research state that the application of group guidance services is effectively used in forming the personality of teenagers in the orphanage. Based on the results obtained, it is known that after implementing the service there was a good change, namely that initially the children tended to close themselves off, now they have started to try and try to open themselves up, this is because The children have received information and understanding about the impacts that will occur if they always isolate themselves from the environment, so that by implementing group guidance it is hoped that they will be able to have a positive influence on the personality of teenagers at the Griya Yatim and Dhuafa Orphanage